The League of Unexceptional Children : the kids who knew too little - Daneshvari, Gitty (League of Unexceptional Children, 2017)
"Utterly average twelve-year-olds Jonathan Murray and Shelley Brown, agents with the League of Unexceptional Children, travel to Europe to infiltrate a secret society and save the day one last time"--